2010
DOI: 10.4061/2010/729391
|View full text |Cite
|
Sign up to set email alerts
|

Ankle Blood Pressure and Pulse Pressure as Predictors of Cerebrovascular Morbidity and Mortality in a Prospective Follow-Up Study

Abstract: Background and Objective. We examined the association of elevated ankle blood pressure (ABP), together with exercise blood pressure, with incident cerebrovascular (CV) morbidity and mortality in a prospective follow-up study of 3,808 patients. The results were compared with pulse pressure, another indicator of arterial stiffness. Methods. Patients with normal ankle and exercise brachial blood pressures were taken as the reference group. Pulse pressure was considered as quartiles with the lowest quartile as the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 32 publications
0
15
1
Order By: Relevance
“…Ankle BP is correlated with arm BP and the augmentation of central BP [15]. Elevated ankle BP was demonstrated as a risk for left ventricular hypertrophy and arterial stiffness, as well as a predictor for future dementia and cardio-cerebrovascular morbidity and mortality [9][11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ankle BP is correlated with arm BP and the augmentation of central BP [15]. Elevated ankle BP was demonstrated as a risk for left ventricular hypertrophy and arterial stiffness, as well as a predictor for future dementia and cardio-cerebrovascular morbidity and mortality [9][11].…”
Section: Discussionmentioning
confidence: 99%
“…A study showed that the leg BP in orthostatic posture is associated with left ventricular mass in normotensive subjects [9]. Furthermore, increased ankle BP is a marker of arterial stiffness or subclinical atherosclerosis, and an independent risk for future dementia, cardio-cerebrovascular morbidity and mortality [10],[11].…”
Section: Introductionmentioning
confidence: 99%
“…Elevated ankle pressures without increased brachial pressures have been associated with increased cardiovascular deaths and death from any cause in Europeans 19. It is postulated that raised ankle pressures due to arterial stiffness precede occlusive vascular disease in the lower limbs 20.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of hypertension is increasing at an accelerated rate not only in adult but in school-age children too. This has raised great concern about premature development of cardiovascular disease, which has important long-term health and financial implications [4][5][6]. Blood pressure (BP) screening may be effective in identifying children with hypertension though evidence is limited and false-positive rates are high [7,8].…”
mentioning
confidence: 99%
“…Pulse pressure is an indicator of the stiffness of large arteries, especially of the aorta. More recently, increased attention has been given to PAP as a predictor of cardiovascular risk [4,5,10]. In the Framingham study it was shown that the systolic blood pressure and pulse pressure reflect arterial stiffness, demonstrated that with increasing age, a gradual shift occurs from diastolic to systolic pressure and then to pulse pressure as predictors of coronary heart disease [6].…”
mentioning
confidence: 99%